Applications of graphene nanomaterials in energy storage—A state-of-art short review - Farhana, K.; K., Kadirgama; S., Subramonian; D., Ramasamy; M., Samykano; Mahamude, A. S. F. (Springer, 2023)
The study presents the usage behavior of graphene in the energy field. Graphene has been comprehensively studied in the energy-related application due to higher conductivity and mechanical flexibility. The architecture of graphene permits it to strengthen and facilitate its application in the energy arena. Herein, the application of graphene in various energy storages such as fuel cells, dye-sensitized solar cells, batteries, nuclear power plants, and thermoelectric has been studied neatly. Graphene reacts towards these substances chemically, mechanically, and electrically to a great extend and appears with the excellent output of these objects. In the future graphene could be applied to the others field of energy and science successfully.